Resource-induced coping heuristics transform psychological capital into opportunity recognition. (April 2023) - Karami, Masoud; Tang, Jintong; Istipliler, Baris; Adomako, Samuel
The current study seeks to contribute to the understanding of entrepreneurial opportunity recognition by focusing on two issues. First, it explores the relationship between entrepreneurs' psychological capital and opportunity recognition. Second, it investigates the mediating mechanism of entrepreneurs' resource-induced coping heuristics in this relationship. Data collected from 208 entrepreneurs (82 were female respondents) in Ghana offered support for our hypotheses. The results show that resource-induced coping heuristics serves as the mechanism that transforms entrepreneurs' psychological capital to new opportunity recognition. This study enhances the understanding of the psychological foundations of entrepreneurial opportunity recognition.